The morphology of saccular otoliths as a tool to identify different mugilid species from the Northeastern Atlantic and Mediterranean Sea - Callicó Fortunato, Roberta Glenda (2014)
In the Northeastern Atlantic and Mediterranean Sea there are 8 species of the Mugilidae family: Mugil cephalus, Liza aurata, Liza ramada, Oedalechilus labeo, Chelon labrosus, Liza saliens, Liza carinata and Liza haematocheila. The identification of mugilids is very important for local fisheries management and regulations, but it is difficult using gross morphological characters. This work aims to contribute to the identification of mullets present in the Northeastern Atlantic Ocean and Mediterranean Sea using saccular otolith features of each species. Specimens of C. labrosus, L. aurata, L. ramada, L. saliens and M. cephalus were obtained from Delta del Ebro (40°38’N–0°44’E) in artisanal catches. For L. carinata and O. labeo photographs extracted from AFORO online database were used. L. haematocheila was not studied for lack of otolith samples. A general pattern of the saccular otoliths for this family was identified: the shape of the otoliths are rectangular to oblong with irregular margins; they present a heterosulcoid, ostial sulcus acusticus, with an open funnel-like ostium to the anterior margin and a closed, tubular cauda, ending towards the posterior ventral corner, always larger than the ostium. In the present study, the mugilid species could be recognized using their saccular otolith morphology. Here we give the first key to identify Northeastern Atlantic and Mediterranean mullets. The distinctive features between the species were the position and centrality of the sulcus, the curvature of the cauda, the presence of areal depositions and plateaus, and the type of anterior and posterior regions. These features could be used not only to reinforce the identification keys through morphological and meristic characters of the species, but also to identify the species consumed by piscivores, being the otoliths the only identifiable remains of the individuals.